STRATEGI PENGEMBANGAN DIGITAL TOURISM DALAM MENINGKATKAN KUNJUNGAN WISATAWAN KE DESA WISATA ALAM ENDAH KECAMATAN RANCABALI, KABUPATEN BANDUNG - Sukmadi Sukmadi; Andar Danova L. Goeltom; Haryadi Darmawan; Violetta Simatupang; Wisnu Bawa Tarunajaya (LPSDI Bina Patria, 2023)
This study aims to identify and analyse digital tourism development strategies in increasing tourist visits to the Alam Endah tourist village, Rancabali District, Bandung Regency. The method used in this study is a descriptive qualitative method with a case study approach. Sources of data in this study are primary funds and secondary data. Primary data were obtained through interviews and field observations. While the data analysis technique used is data analysis using the interactive model of analysis developed by Miles and Hubermann. The results showed that (1) the digital tourism development strategy in the Alam Endah tourism village was still focused on the use of social media such as Instagram, Tiktok, Facebook and other social media; (2) factors that influence the increase in tourist visits to the Alamendah Tourism Village include tour packages for glamping activities and sports tourism as well as plantation tourism; (3) The digital tourism development strategy can increase tourist visits to the Alamendah Tourism Village, this is marked by the increasing number of reservations and access traffic through the Jadesta website and other digital media.